A color-digit Stroop task shows numerical influence on numerosity processing. - Hershman, Ronen; Beckmann‏, Lisa; Keha, Eldad; Wagner, Michael; Kaufmann, Liane; Henik, Avishai (Memory & Cognition, 2025)
The numerical Stroop task involves presenting participants with two digits that differ in physical size and numerical value and asking them to report which digit had the larger size or value while ignoring the other dimension. Previous studies show that participants have difficulty ignoring the irrelevant dimension and thus have implications on the automaticity of numerical processing. The present study investigates the automatic influence of numerical value on numerosity processing in a novel Stroop-like task. In two experiments, participants were presented with digits made of colored stripes and asked to identify the number of different colors. In both experiments, interference and facilitation effects were found, supporting the automaticity of symbolic number processing and its influence on numerosity processing. These findings expand upon previous research on numerical as well as counting Stroop tasks, and have potential implications for studying interference and basic numerical processing in children and clinical populations.